"The Mister did talk to me but I didn't understand what he said!": A semiotic anthropologic approach to reflexive discourse about language in a rural environment. (Signifiances (Signifying), 2021)
Stemming from ethnographic work conducted in the southwest of the Allier district in France (Auvergne-Rhône-Alpes Region), this article offers an application of some key concepts in North-American semiotic anthropology (Parmentier 1994, 2006). Through the analysis of an interaction where others’ discourse is performed, it will show the importance of taking into account processes of attributing meaning to space and time, known as chronotopic formulations (Agha 2015), to understand the hierarchization of ways of talking through reflexive discourse about langage.